Experience with using intravenous clonidine hydrochloride in the critical care unit of a tertiary hospital in Spain. Issue 2 (12th March 2012) - Motos, M.A.; Saavedra, V.; Alcántara, S.; García, E.; Valdivia, M.; Romera, M.A.
Abstract : Background: Clonidine hydrochloride is an α-2 agonist whose approved indication in the summary of product characteristics is as an antihypertensive; nevertheless other indications could be possible. Purpose: To examine the 'off label' indications of clonidine in critical care patients on mechanical ventilation, in a tertiary hospital. To describe the procedure to obtain intravenous clonidine hydrochloride in our hospital, since it is not marketed in Spain. Materials and methods: Retrospective study of the use of intravenous clonidine in continuous infusion, for critically-ill patients, in the first six months of 2010. The Selene and Picis programmes were used to analyse computerised clinical histories. Results: A total of 18 patients were treated with clonidine. In 16.7% of the cases, it was used as antihypertensive, and in the remaining 83.3% cases, its use was 'off label'. In 33.3% of the cases, it was used to control withdrawal symptoms, in 27.8% to prevent withdrawal when removing sedation, in 16.7% to contribute to sedation and in 5.5% to treat delirium. The range of doses used in intravenous perfusion was 0.3-9 mcg/Kg/h. The average length of treatment was 6.8 days. In 94.4% of patients, it was used in combination with other sedatives; it was used as monotherapy in only 5.5% of the cases. It was combined with propofol in 77.7% of cases, with midazolam in 33.3%, with fentanyl in 22.2%, with remifentanil in 22.2% and with morphine in 11.1% of cases. 27.7% of the patients responded with hypotension and 0.05% with bradycardia. Acquisition of intravenous clonidine in Spain must be through importation from abroad or by requesting it as a 'special' from accredited pharmacies. The authors acquire it produced in small amounts in this way in concentrations of 0.15 mg/ml and 0.4%, 5 ml ampoules. Conclusions: In our patients, intravenous clonidine hydrochloride has been shown to be a useful drug for controlling tolerance to, or withdrawal from, sedative and analgesic drugs in critically-ill patients undergoing mechanical ventilation.